BONE MINERAL DENSITY IN SJOGREN'S DISEASE - N S Sliornikova; V I Vassiliev; A V Smirnov (Научно-практическая ревматология)
Objective. To study mineral density of bone tissue (BMD) in female pts with Sjogren's syndrome (SS) depending on menstrual statute and to evaluate the effect on it of long-term (for 5 years and more) therapy by prednizolone in dosage 2.5-5 mg/day on the state of bone tissue. Material and methods. 120 female pts aged 30-63 were examined by densitometry of low back and femoral neck with «Hologic 1000». Results. Comparison of obtained results with reference base data enabled to reveal negative effect of prednizolo- nc on bone tissue mineralization, clearly demonstrated at the beginning of glucocorticosteroid therapy in peri- menopausa. It was also noted that menopausa began earlier in pts taking prednizolone (at 43.9±5.1 y/o) as compared with untreated ones (at 4S.9±4.5 y/o); there were notable effect of the age of menopausa beginning on BMD and lower effect of the duration of postmenopausa. Rare (3.3%) development of osteoporosis in women of reproductive age associated with long-term non-correctable hypergammaglobulinemia and damage of renal tubular apparatus.